Root-shoot growth and time to transplant of different lettuce genotypes during nursery - Di Benedetto, Adalberto; Carnelos, Danilo; Lozano Miglioli, Jorge; Fujinuma, Pablo; Giardina, Ernesto (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2021)
Although vegetable nursery growers decide on plug sizes based on the types, production time and schedule of the crops to grow, they usually choose individual small cell sizes because these allow short plant-raising periods and reduced costs. However, larger plugs produce a finished plant after transplant in a shorter period of time than smaller plugs. Nursery growers end the propagation period when roots take up the plug cell and plantlets can be removed from the plug tray without damage. Thus, this study aimed to investigate the effect of three plug-cell sizes and a single BAP application (100 mg L-1) on the shoot and root growth and time to transplant of different lettuce genotypes. Nursery decreased as plug cell volume increased and with the single BAP spray. A novelty result was that the transplant dates were assigned when the marginal root dry weight accumulation decreased, i.e., based on objective rather than on subjective observations. The significant leaf area and dry weight accumulation found could be explained by growth parameters such as the rate of leaf appearance, the relative rate of leaf area expansion, the relative growth rate, the net assimilation rate and the partition coefficient from root: shoot allometries. Highlights Root restriction due to small plugs in transplant trays delay lettuce transplant. Exogenous cytokinin (BAP) overcame root restriction and decreased time to transplant. Time to transplant can be addressed on an objective basis: it were assigned when the marginal root dry weight accumulation decreased.